The impact of tumor immunogenicity on cancer pain phenotype using syngeneic oral cancer mouse models - Horan, Nicole L.; McIlvried, Lisa A.; Atherton, Megan A.; Yuan, Mona M.; Dolan, John C.; Scheff, Nicole N. (Frontiers in Pain Research, 2022)
Head and neck squamous cell carcinoma (HNSCC) patients report severe function-induced pain at the site of the primary tumor. The current hypothesis is that oral cancer pain is initiated and maintained in the cancer microenvironment due to secretion of algogenic mediators from tumor cells and surrounding immune cells that sensitize the primary sensory neurons innervating the tumor. Immunogenicity, which is the ability to induce an adaptive immune response, has been widely studied using cancer cell transplantation experiments. However, oral cancer pain studies have primarily used xenograft transplant models in which human-derived tumor cells are inoculated in an athymic mouse lacking an adaptive immune response; the role of inflammation in oral cancer-induced nociception is still unknown. Using syngeneic oral cancer mouse models, we investigated the impact of tumor cell immunogenicity and growth on orofacial nociceptive behavior and oral cancer-induced sensory neuron plasticity. We found that an aggressive, weakly immunogenic mouse oral cancer cell line, MOC2, induced rapid orofacial nociceptive behavior in both male and female C57Bl/6 mice. Additionally, MOC2 tumor growth invoked a substantial injury response in the trigeminal ganglia as defined by a significant upregulation of injury response marker ATF3 in tongue-innervating trigeminal neurons. In contrast, using a highly immunogenic mouse oral cancer cell line, MOC1, we found a much slower onset of orofacial nociceptive behavior in female C57Bl/6 mice only as well as sex-specific differences in the tumor-associated immune landscape and gene regulation in tongue innervating sensory neurons. Together, these data suggest that cancer-induced nociceptive behavior and sensory neuron plasticity can greatly depend on the immunogenic phenotype of the cancer cell line and the associated immune response.